IMPLEMENTASI ALGORITHM CNN DAN SLTM UNTUK TRANSLATOR THINGS - Al Abdul Rohim; Taufiq Nashrullah; Anggit Dwi Hartanto; Hartatik (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Translator Things is a technology that allows users to find out the names of objects in a variety of foreign languages, by using a cellphone / laptop camera, Translator Things is very useful if we are abroad and we can find out the name of the object that our country is visiting. For the System we use CNN and LSTM as CNN's algorithm to identify objects on the camera, and LSTM to translate text on the identification of these objects The results of this discussion will identify objects that will be identified through text.